2020
DOI: 10.1186/s12885-020-07636-0
|View full text |Cite
|
Sign up to set email alerts
|

The age threshold of the 8th edition AJCC classification is useful for indicating patients with aggressive papillary thyroid cancer in clinical practice

Abstract: Background Papillary thyroid cancer (PTC) is unique among cancers in that patient age is a consideration in staging. One of the most important modifications in the 8th Edition of the American Joint Committee on Cancer (AJCC) classification is to increase the age cut off for risk stratification in PTC from 45 to 55 years. However, whether this cut off is useful in clinical practice remains controversial. In the present study, we assessed how well this new age threshold stratifies patients with aggressive PTC. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In most studies, age has been reported as one of the most important and effective risk factors for the survival of the disease in patients with thyroid cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, age has been reported as one of the most important and effective risk factors for the survival of the disease in patients with thyroid cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“… 34 It was supported by our results. 35 Studies have assessed that a higher age cutoff rather than a previously estimated 45 years old improves the accuracy of the prognostic system and therefore should decrease the overtreatment rate of patients. 35 In the present study, we found that younger age of the patient with AUS/FLUS diagnosis was an independent predictor for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Studies have assessed that a higher age cutoff rather than a previously estimated 45 years old improves the accuracy of the prognostic system and therefore should decrease the overtreatment rate of patients. 35 In the present study, we found that younger age of the patient with AUS/FLUS diagnosis was an independent predictor for malignancy. We observed a statistically significant difference in the ROM between the patients below 55 years old and those 55 years old and older.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with classic PTC, mean age at diagnosis was found to be 48 years, whereas in our cohort of HPTC the mean age was higher, i.e., 51.3 years [ 48 ]. Older age is a known negative predictive factor for survival, and this was also confirmed in the case of HPTC, with older age correlating with reduced survival [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 92%